Photovoltaic Industrial Systems An Environmental Approach - Papadopoulou, Elena. (Green Energy and Technology, 2011)
This book investigates the existing situation of photovoltaic systems regarding environmental questions and energy efficiency in the European Industry, particularly the industrial units at the Greek area. A model of energy management based on economical, technical and administrative aspects is proposed in order to combine industrial uses of photovoltaics with environment protection.